SUMO: Glue or Solvent for Phase-Separated Ribonucleoprotein Complexes and Molecular Condensates? - Keiten-Schmitz, Jan; Röder, Linda; Hornstein, Eran; Müller-McNicoll, Michaela; Müller, Stefan (Frontiers in Molecular Biosciences, 2021)
Spatial organization of cellular processes in membranous or membrane-less organelles (MLOs, alias molecular condensates) is a key concept for compartmentalizing biochemical pathways. Prime examples of MLOs are the nucleolus, PML nuclear bodies, nuclear splicing speckles or cytosolic stress granules. They all represent distinct sub-cellular structures typically enriched in intrinsically disordered proteins and/or RNA and are formed in a process driven by liquid-liquid phase separation. Several MLOs are critically involved in proteostasis and their formation, disassembly and composition are highly sensitive to proteotoxic insults. Changes in the dynamics of MLOs are a major driver of cell dysfunction and disease. There is growing evidence that post-translational modifications are critically involved in controlling the dynamics and composition of MLOs and recent evidence supports an important role of the ubiquitin-like SUMO system in regulating both the assembly and disassembly of these structures. Here we will review our current understanding of SUMO function in MLO dynamics under both normal and pathological conditions.